SAP GRC for dummies - Broady, Denise Vu; Roland, Holly A. (--For dummies., 2008)
Governance, risk, and compliance--these three big letters can add up to one giant headache. But GRC doesn't have to be a boil on your corporate behind. SAP GRC For Dummies untangles the web of regulations that confronts your company and introduces you to software solutions the not only keep you in compliance, but also make your whole enterprise stronger. This completely practical guide starts with a big-picture look and GRC and explains how it can help your organization grow. You'll find out why these regulations were enacted; what you can do to ensure compliance; and how compliance can help yo.